Pengaruh Ukuran Perusahaan, Profitabilitas Dan Struktur Kepemilikan Terhadap Corporate Social Responsibility Disclosure (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2009-2012) - Nuraeni, Nuraeni; A, Eko Agus (Arthavidya Jurnal Ilmiah Ekonomi, 2014)
The company in its business activities account for not only theinvestors and management but also in the wider community . Therefore,companies are required to provide information about the company moretransparent . The information is contained in the annual reports of publiclisted companies . It is expected that the annual report can be a medium ofcommunication between the company and the community . This study aims toanalyze and provide empirical evidence of the effect of firm size ( Size ) ,profitability and ownership structure on corporate social responsibilitydisclosure .This study is a quantitative model using multiple regressionanalysis to determine the direction and effect relationship dependent andindependent variables . Multiple regression analysis performed on the datatime series over the period 2009-2012 on the companies listed in IndonesiaStock Exchange ( IDX ). From the data analysis carried Based on the tableabove hypothesis were conducted by F test is test simultaneously (simultaneous ) shows the significant value of 0.010 ( P <0.05 ) , it can beconcluded that there is a significant effect of simultaneous variables X1 , X2 ,X3 , and X4 to Y. in other words , the resulting regression models used topredict viable future . It can be concluded that Y is determined by factors X1 ,X2 , X3 , and X4 , which is described in the regression equation : Y = -0088 +0.011 X1 + 0.056 X2 -0256X3 -0110X4 .To indicate whether the individual independent variables have a significantinfluence on the dependent variable we used the t test ( partial test ) . Basedon the research results , by taking the real level ( significance ) of 5 % ( 0:05 ), for constants obtained significance value ( p) of 0.000 ( P <0.05 ) , it can beconcluded that the constant significantly influence the regression model . Forvariables X1 , X3 , and X4 respectively indicate significance value in a row of0000 , 0.048 , and 0.013 . It can be concluded that the X1 , X3 , and X4 have asignificant influence on Y. While partial and X2 does not have a significanteffect partially on Y.Keywords : company size , profitability , ownership structure , corporatesocial responsibility disclosure